2000
DOI: 10.1063/1.126756
|View full text |Cite
|
Sign up to set email alerts
|

Shock-induced transformation of β-Si3N4 to a high-pressure cubic-spinel phase

Abstract: β- Si 3 N 4 powders were shock compressed and quenched from 12 to 115 GPa. β-Si3N4 transforms to the spinel-type Si3N4 (c-Si3N4) by a fast reconstructive process at pressures above about 20 GPa. The yield of c-Si3N4 recovered from 50 GPa and about 2400 K reaches about 80% and the grain sizes are about 10–50 nm. It is proposed that the fast transformation to c-Si3N4 occurs by rearrangement of nitrogen stacking layers, which initiates partial breakup of the SiN4 tetrahedra and formation of SiN6 octahedra at high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
84
0
4

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(92 citation statements)
references
References 13 publications
4
84
0
4
Order By: Relevance
“…Experiments showed that the cubic spinel γ-Si 3 N 4 can be obtained from both hexagonal α-and β-Si 3 N 4 upon com-pression and simultaneous in situ heating. [3][4][5][6][7] The γ phase is quenchable to the ambient condition, and it remains stable at temperatures ranging up to about 1670 K at ambient pressure. 23,24 When γ-Si 3 N 4 "decomposes" at ambient pressure upon heating, the samples may consist of both α-and β-Si 3 N 4 .…”
mentioning
confidence: 99%
“…Experiments showed that the cubic spinel γ-Si 3 N 4 can be obtained from both hexagonal α-and β-Si 3 N 4 upon com-pression and simultaneous in situ heating. [3][4][5][6][7] The γ phase is quenchable to the ambient condition, and it remains stable at temperatures ranging up to about 1670 K at ambient pressure. 23,24 When γ-Si 3 N 4 "decomposes" at ambient pressure upon heating, the samples may consist of both α-and β-Si 3 N 4 .…”
mentioning
confidence: 99%
“…Consequently, the study of the transition from low pressure phases (α, β) to a high density c-phase and the construction of silicon nitride phase diagram are of importance as it will allow optimizing the conditions of the cphase synthesis in shock and detonation waves. It was found in [2] that the increase in temperature in recovery shock experiments brings down the transformation pressure threshold to the c-phase. To further investigate this phenomenon we constructed a Hugoniot and a sound velocity pressure dependence curve for porous silicon nitride samples, which allowed us to reach higher temperatures under shock loading.…”
Section: Introductionmentioning
confidence: 99%
“…In 1999 the A. Zerr group [1] synthesized a new high density c-Si 3 N 4 modification with a cubic crystalline structure in several tens of nanograms in a laser heating diamond anvil cell at 15 GPa and 2800 K from a low pressure Si 3 N 4 modification. Later the same modification was synthesized by shock wave [2] and detonation [3] methods. The determined bulk modulus of c-Si 3 N 4 was about 300 GPa and the hardness exceeded 35 GPa [4] which is slightly higher than for SiO 2 -stishovite (about 33 GPa) [5] often referred to as the third hardest material after diamond and cubic boron nitride [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Different preparation methods have also been developed. Recently, Sekine et al 15,17 have prepared ␥-Si 3 N 4 by shock-induced transformation of ␤-Si 3 N 4 powder, which may produce ␥-Si 3 N 4 in large scale.…”
Section: Introductionmentioning
confidence: 99%